CLIL approach in encouraging self-efficacy amongst Malaysian gifted students for Arabic tasks accomplishment - M.S., Kamis; M.J., Ismail; M.N., Jais; D., Mikeng; S.G., Zainal Abidin; R., Yusuf (Journal of Language and Linguistic Studies, 2021)
CLIL approach refers to Content and Language Integrated Learning. This paper discusses the self-efficacy of Malaysian Gifted Students (MGS) at GENIUS@Pintar Negara in understanding Arabic tasks in the classroom, for example, understanding the Arabic terms in the lesson of Haji. These terms are; a) dam tertib and takdir, b) dam tertib and ta’dil, c) dam takhyir and takdir, d) dam takhyir and ta’dil. Besides, by employing the CLIL, the MGS can improve themselves because the CLIL approach encourages their self-efficacy to completely deal with the language task. The present study employs; qualitative study by using an interview, verbal report, and observation. This method is an instrument to answer two research questions. a) How the individual of MGS adapts his/ her situation to understand the four Arabic terms of the dam in Haji after undergo the three principles stages of classroom task in CLIL? b) What is the best method to memorize the four Arabic terms of the dam in Haji? In this study, three participants took part in the pilot study, and seven participants took part in the actual study. The present study revealed that the MGS in the Pusat GENIUS@Pintar Negara prefer to be independent learners by using the internet to understand the four Arabic terms and memorize by using keywords related to the four Arabic terms in performing Haji.